(untitled) (Quaestiones Disputatae: temas en debate, 2018)
This text begins by deﬁning civic education from its connection with a conception of a citizenship that is sensitive, in its very formulation, to the reality of those who suffer. Next, the thesis is argued that victims should be a central reference for civic education. In a third step, as a preparation to apply this thesis to situations of transition, from politically motivated violence in a country to the cessation of it, those transitional contexts are described in those aspects that are relevant for their ethical-educational confrontation. Finally, it speciﬁes how and what beneﬁts the active presence of the victims can bring in civic education, attentive to transitional situations; this is carried out along the lines of the presentation of an educational experience in the Basque Country (Spain), while at the same time keeping in mind the current Colombian transition.